2017
DOI: 10.7196/samj.2017.v107i12.12539
|View full text |Cite
|
Sign up to set email alerts
|

Geographical maldistribution of surgical resources in South Africa: A review of the number of hospitals, hospital beds and surgical beds

Abstract: Corresponding author: A J Dell (angelajdell@gmail.com) Background. The global burden of surgical disease has been studied to a limited extent. Despite the proven benefits of surgery, surgical services remain poorly resourced. Contributing to this global crisis is the critical lack of data regarding available resources. Objective. To analyse the distribution of some resources necessary for the provision of surgical care. The distribution and number of surgical resources (number of surgical beds) relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…South Africa had about 3,000 (out of about 7,000) critical care beds available between the public and private healthcare sectors reserved for critical COVID-19 patients [ 13 ]. A study done in 2017 showed that nationally, there was 1 hospital, 187 hospital beds, and 42 surgical beds per 100,000 population [ 14 ]. South Africa had the most number of COVID-19 infections in the whole of Africa, with a total of 2,272 cases as of April 13, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…South Africa had about 3,000 (out of about 7,000) critical care beds available between the public and private healthcare sectors reserved for critical COVID-19 patients [ 13 ]. A study done in 2017 showed that nationally, there was 1 hospital, 187 hospital beds, and 42 surgical beds per 100,000 population [ 14 ]. South Africa had the most number of COVID-19 infections in the whole of Africa, with a total of 2,272 cases as of April 13, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison with available surveillance data, the NICD's TRAC-South Africa passive laboratorybased surveillance programme -which included just 11 public sector hospitals and 85 private sector hospitals -reported 2 172 cases of candidaemia over a 19-month period in 2009 and 2010. [37] However, there are at least 544 hospitals in SA, [88] suggesting that our estimate is reasonable. In the TRAC-South Africa surveillance, approximately a quarter of isolates were from neonatal ICUs, [89] and these were not incorporated into our estimates.…”
Section: Researchmentioning
confidence: 76%
“…South Africa has a two-tier healthcare system, comprising state-funded hospitals that provide healthcare services to individuals who do not have health insurance, and private hospitals that provide healthcare to those who can afford the services or have private health insurance (Young 2016 ). The state-funded hospitals provide healthcare to 80% of the population who reside in rural, urban and unplanned, temporary housing settlements, surrounding the hospitals (Dell & Kahn 2017 ). According to Krugg and Alarcos ( 2017 ), the two-tiered healthcare system is characterised by mal-distribution of resources where private hospitals are generally better equipped in terms of resources, staffing and infrastructure.…”
Section: Methodsmentioning
confidence: 99%